Stereoselective synthesis of the densely functionalized C1-C9 fragment of amphidinolides C and F - Mohapatra, Debendra K.; Dasari, Pavankumar; Rahaman, Hasibur; Pal, Rita (Tetrahedron Letters, 2009)
The synthesis of the C1-C9 subunit of amphidinolides C and F is described. Key steps include tandem Sharpless asymmetric dihydroxylation-S(N)2 cyclization reaction, Lewis acid-mediated epoxide opening, Wittig reaction, and Wacker oxidation. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Amphidinolide C and F; Cytotoxic; Tandem dihydroxylation-S(N)2; Wacker oxidation; Wittig reaction